HUBUNGAN SOSIAL DAN KEPERCAYAAN DIRI SISWA YANG MEROKOK DI MTS AL MUTTAQIN PEKANBARU - Marta, Yoara Amelia; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The phenomenon in schools today, both in public schools and private schools, many children fill their free time by smoking. Nowadays smoking behavior is a behavior that has been commonly encountered. Smokers come from various social classes, different statuses and various age groups. This might be because cigarettes can be easily obtained and obtained anywhere. The objectives of this study are: To find out the description of social relationships of students who smoke in MTS Al Muttaqin Pekanbaru. To find out an overview of the confidence of students who smoke in MTS Al Muttaqin Pekanbaru. To find out the relationship between social relations and self-confidence of students who smoke in MTS Al Muttaqin Pekanbaru. Time of study in May 2018 in the 2017/2018 school year. The research method used in this research is quantitative descriptive method. The population in this study amounted to 74 students. The study sample was 22 students. Based on the results of the research conducted, it can be concluded that: communication and social contact (social contact) have a big contribution in supporting the social relations of students who smoke. various aspects support the improvement of self-confidence of students who smoke such as mental and physical conditions, adaptation and communication, family education background, life experience, etc. have a big contribution in supporting their self-confidence.Keywords: smoking, social interaction, self confidence.